Supervision of Class Visits By The Principal in Developing Teacher Competencies at SDIT Makassar Islamic School Baruga - Nuraisyah Nuraisyah; Nurjannah Nurjannah (Yayasan Insan Mulia Bima, 2023)
The quality of teachers in Indonesia values are still concerning, this can be seen from the current level of teacher competence. The results of the competency test conducted by Sumana Supranata in 2015 showed that there was still a lack of competence of teachers in the field of pedagogical competence. One of the efforts made related to educators is by supervising. The implementation of supervision provides a role in maintaining and improving the competencies of educators. This research aims to find out related to the supervision of visits carried out by the principal to maintain teacher competence. The approach used is descriptive qualitative with a case study design at the principal of SDIT Makassar Islamic School Baruga. The results of the study showed that, supervision of class visits carried out with the stages of: (a) The preparation process; (b) implementation; and (c) evaluation and control. The coaching is carried out by: (a) conducting teacher competency training; (b) hold ta'lim. Then in assessing and increasing the motivation of teacher competencies, certain ways are applied, namely: (a) making teacher report cards; (b) choose a best teacher.